Classical Labeling of Bacterial Pathogens According to Their Lifestyle in the Host: Inconsistencies and Alternatives - Silva, Manuel T. (Frontiers in Microbiology, 2012)
An ample understanding of the complex interactions between host and pathogen will improve our ability to develop new prophylactic and therapeutic measures against infection. Precise classification of infectious agents in regards to their infective lifestyles in the host and corresponding pathogenic implications are required because clear concepts are essential to plan fruitful research. Classically, pathogenic bacteria are classified as extracellular, facultative intracellular, and obligate intracellular. In my opinion, this classification is inadequate because, as concluded from data here discussed, it is based on inconsistencies and hyper-valorizes the capacity of the infectious agent replicate in vitro in cell-free media. For a microbial pathogen, what matters is whether intra- or extracellularity is in the context of the in vivo life and in association with pathogenicity. When living as a pathogen in association with its host, what is relevant in microbiological terms is not the ability to grow in artificial cell-free bacteriological media or in environmental niches but whether the intracellular infectious agent, besides the phase of intracellular growth which is behind its label, also is able to live extracellularly in the natural settings of the extracellular territories of their hosts. To eliminate the inconsistencies associated with the classical labeling of bacterial pathogens, I propose that bacterial pathogens be labeled exclusive extracellular, dual intracellular/extracellular and exclusive intracellular based on their infective lifestyle in the host, not in the ability to grow in artificial bacteriological media.